Genetically engineered bacterium: Principles, practices, and prospects - Liu, Yiting; Feng, Jing; Pan, Hangcheng; Zhang, Xiuwei; Zhang, Yunlei (Frontiers in Microbiology, 2022)
Advances in synthetic biology and the clinical application of bacteriotherapy enable the use of genetically engineered bacteria (GEB) to combat various diseases. GEB act as a small 'machine factory' in the intestine or other tissues to continuously produce heterologous proteins or molecular compounds and, thus, diagnose or cure disease or work as an adjuvant reagent for disease treatment by regulating the immune system. Although the achievements of GEBs in the treatment or adjuvant therapy of diseases are promising, the practical implementation of this new therapeutic modality remains a grand challenge, especially at the initial stage. In this review, we introduce the development of GEBs and their advantages in disease management, summarize the latest research advances in microbial genetic techniques, and discuss their administration routes, performance indicators and the limitations of GEBs used as platforms for disease management. We also present several examples of GEB applications in the treatment of cancers and metabolic diseases and further highlight their great potential for clinical application in the near future.